A equalização da competição no comércio internacional: uma abordagem pela análise econômica do direito - Paulo Henrique Teixeira Rage (2023)
The subject of the international trade is gaining even more relevance in an international economic scenario of globalization of markets and reduction of trade barriers. However, periodically, legislators and governments question the free trade and/or the protectionist measures, under arguments that are often subjective, such as “unfair trade”. This has led to situations ranging from lack of effective free competition to trade wars. Faced with this subject-problem, the objective of this research is to identify which legal-tax rule on international trade is more efficient from an economic and competition point of views. This research aims to demonstrate the economic and competitive ineffectiveness of the current legal-tax rules; and, to propose a new general rule that can allow economic (maximization of wealth) and competition (protection of competition) efficiencies in international trade. In order to achieve such objectives proposed, it has as starting point the understanding of Milton Friedman, as the theoretical framework, on the economic efficiency of free trade and the importance of protecting competition. Throughout this thesis, will be analyzed the antagonistic theories about international trade; the foundations of the free market and its economic efficiency; the fundamentals of free competition; and, is performed the practical application of the proposed legal rule in concrete cases, through the methodological tools of the economic analysis of the law and the comparative law. The hypothesis adopted is the statement that it is possible to establish a general legal rule, by means of the reorganization of the already existing taxes, in a way that preserves economic efficiency and competition in international trade. This rule, therefore, would: allow the economic efficiency of the free market; and, preserve free competition between domestic and foreign producers. We intend to name this hypothesis as the “Equalization of Competition in International Trade”. The methodology used involves: historical, doctrinal, and legislative analysis; comparative law; and, above all, the tool of economic analysis of law, aiming and presenting, in the end, the results obtained.